Keterampilan Membaca Dalam Pembelajaran Bahasa Indonesia dan Sastra Anak Pada Kurikulum Merdeka di Sekolah Dasar - Saputri, Andi Aprilia; Diana, Erlin; Irawan, Dadang; Husain, Alma Pratiwi (Sindoro: Cendikia Pendidikan, 2025)
Reading is an activity carried out by the reader to understand the message that wants to be conveyed through writing or words. The purpose of this study is to analyze and explore effective strategies in improving reading skills, as well as identify factors that influence the improvement of reading skills of elementary school students. The preparation of this article uses a literature study method related to research and other references such as books, magazines, and literature. effective strategies carried out by teachers are Reading Literacy Activities, Spelling Strategies, and Extensive reading strategies by using these strategies students will be easier in improving reading skills. Factors that influence students' reading delays are the lack of guidance and motivation from parents.